Model for evaluating the performance of elementary school teachers using the analytical hierarchy process - Sri Wiyati Mahrani; Desty Endrawati Subroto; Moh. Gifari Sono; Herman Titop; Tukiyo Tukiyo (Jurnal Mantik, 2023)
The significance of analyzing teacher performance in order to develop future competency, which might lead to rewarding teachers who have been evaluated according to established assessment criteria. Numerous studies have been conducted to aid in the process of evaluating teacher performance, revealing that the problem of evaluating teacher performance involves multi-attribute decision making problems; therefore, this study aims to use the AHP method as a decision support method due to the benefits of AHP in describing the relationship between criteria, attributes, and alternatives via a decision hierarchy structure. The evaluation standards include Discipline (C1), Service Orientation (C2), Integrity (C3), and Cooperation (C4) (C4). The results demonstrated that there are recommendations for decision results, namely determining the priority weight of the criteria so that the value of each alternative can be maximized in each criterion, with assessment techniques tailored to the existing business processes in each school. The determination of objective criteria priority weights can also influence the final ranking results of the evaluation of elementary school teachers' performance.